Analisis Sistem Pencatatan Akuntansi pada Pengelolaan Keuangan Masjid: Studi Kasus: Masjid Al-Hidayah Medan Perjuangan, Sumatera Utara - Hariyatih, Suri; Utami, Ranti Juni (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This study aims to analyze the process of recording mosque financial accounting based on Islamic law, namely the Al-Qur’an and Hadith. The object of this research is the Al-Hidayah mosque, kec. Medan Struggle, Medan, North Sumatra. This study uses a qualitative method with a descriptive approach. This study uses data collection techniques through interviews, observation and documentation. As for the informants, namely the secretary as well as the deputy treasurer of the mosque and the mosque adviser. The results of this study indicate that the process of recording financial accounting at the Al-Hidayah mosque is very simple but works as it should in the context of the hadith and the Qur’an but has not implemented PSAK No. 45 because the administrators do not know the term, the mosque administrators are very trustworthy in run it, namely being responsible for what is done, honest and open in terms of submitting financial reports.